Distribution of integrons and phylogenetic groups among highly virulent serotypes of Klebsiella pneumoniae in a Chinese tertiary hospital - Wenjian Liao; Dan Li; Fangpeng Liu; Fang-ling Du; Dan Long; Wei Zhang; Yang Liu (Journal of Global Antimicrobial Resistance, 2020)
Objectives: This study describes the distribution of integrons and phylogenetic groups among clinical highly virulent serotype (HVS) Klebsiella pneumoniae isolates in a Chinese tertiary hospital. Methods: Class 1, 2 and 3 integrases were identified by PCR in 90 clinical isolates of HVS K. pneumoniae. Antimicrobial susceptibility was determined by the disk diffusion method. Multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) were used to analyse the genotypes of the HVS K. pneumoniae isolates. Results: Serotypes K1, K2, K20, K54 and K57 accounted for 54.5%, 21.1%, 1.1%, 18.9% and 4.4% of the 90 isolates. Among the 50 integron-positive isolates, 48 (96%) and 2 (4%) were classified as having class 1 (intI1) and class 2 (intI2) integrons, respectively. Gene cassettes encoding resistance to trimethoprim (dfr) and aminoglycosides (aac, aad) were found to be predominant in class 1 integrons. In addition, the most prevalent sequence type (ST) among the HVS K. pneumoniae isolates was ST23 (49/90; 54.4%), followed by ST29 (11/90; 12.2%), ST86 (10/90; 11.1%), ST65 (9/90; 10.0%), ST15 (6/90; 6.7%), ST412 (4/90; 4.4%) and ST34 (1/90; 1.1%). Conclusion: In summary, a high prevalence of integrons (55.6%) was found among HVS K. pneumoniae isolates in a Chinese tertiary hospital. Class 1 integrons were the most predominant and their variable regions were polymorphic. The presence of integrons in HVS K. pneumoniae isolates results in increased antimicrobial resistance.